Obowiązek raportowania schematów podatkowych a tajemnica zawodowa doradców podatkowych - Ney, Jan (Uniwersytet Wrocławski. Wydział Prawa, Administracji i Ekonomii, 2019)
The article describes the main assumptions of implementation the DAC6 Directive in the field of reporting tax schemes. Historically, the basis for developing regulations was preventing aggressive tax optimization. The final shape of regulations requires reporting all tax schemes that meet specific criteria, where one of the main goals is to obtain a tax benefit (regardless of whether the activity is aggressive tax optimization). The article illustrates the complexity of regulated matter and shows the issues related to reporting tax schemes by tax advisors in the context of the legal assistance and professional secrecy protection.
Keywords: tax schemes; aggressive tax optimization; professional secrecy of a tax adviser; MDR; DAC6